2022
DOI: 10.4067/s0718-58392022000100146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous straw return and fertilization on rice lodging resistance

Abstract: As a common problem in rice (Oryza sativa L.) production, lodging will not only increase harvest costs and reduce rice production, but also affect rice taste seriously and reduce its commercial value. There is still a lack of systematic research on the effect of lodging resistance of rice after returning wheat (Triticum aestivum L.) straw to the field. The study evaluated the effects of continuous straw returning and different fertilizer input levels on the lodging resistance of rice stalks based on years of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, reducing plant height and shortening the internode length of the stem improves the flat rate and cavity area, and consequently improves the lodging resistance of rice (Luo et al, 2007). Zhao et al (2022) showed that returning straw to the field improves the stem wall thickness, stem thickness, and also the bending resistance of the basal internodes. Under the same fertilization treatment, returning straw significantly improved the bending resistance of stems (up to 33.74%), and also the lodging index was reduced by up to 33.86%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing plant height and shortening the internode length of the stem improves the flat rate and cavity area, and consequently improves the lodging resistance of rice (Luo et al, 2007). Zhao et al (2022) showed that returning straw to the field improves the stem wall thickness, stem thickness, and also the bending resistance of the basal internodes. Under the same fertilization treatment, returning straw significantly improved the bending resistance of stems (up to 33.74%), and also the lodging index was reduced by up to 33.86%.…”
Section: Discussionmentioning
confidence: 99%
“…In order to get higher yield, excessive application and/or overuse of nitrogenous fertilizer by the farmers is making the rice crop more prone to lodging and environmental pollution (L. Li, Tian, et al., 2021; Zhang et al., 2014). Interestingly, the consumers’ demand for high‐quality rice is increasing day‐by‐day, whereas rice cultivars with premium grain qualities have poor resistance against lodging (Q. Zhao et al., 2022). Therefore, it is imperative to improve the rice lodging resistance through some easily adoptable management strategies.…”
Section: Introductionmentioning
confidence: 99%